Energy and Sustainability V 2014
DOI: 10.2495/esus140191
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on ground material absorptivity for solar chimney power applications

Abstract: A solar chimney power plant utilizes the ground as its energy conversion medium from solar radiation to kinetic energy in the adjacent air stream. In this work, the conversion capability of six different ground materials, that are potentially available in Malaysia, were studied experimentally and numerically. An experimental setup was constructed to acquire measured data. A numerical model was constructed in the FLUENT software environment to model and simulate the energy conversion process. The selected mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The absorptivity of the collector absorber is of high importance in the performance of the SCPP collector, and thus selecting a suitable type of ground material from the ones that are potentially available is vital in gaining the maximum available energy in the collector. In the present work, which experimentally and numerically extend the work presented by Al-Azawie et al [22]. The absorptivity of different types of ground materials was studied.…”
Section: Numerical Attemptssupporting
confidence: 69%
See 1 more Smart Citation
“…The absorptivity of the collector absorber is of high importance in the performance of the SCPP collector, and thus selecting a suitable type of ground material from the ones that are potentially available is vital in gaining the maximum available energy in the collector. In the present work, which experimentally and numerically extend the work presented by Al-Azawie et al [22]. The absorptivity of different types of ground materials was studied.…”
Section: Numerical Attemptssupporting
confidence: 69%
“…The simulated model showed good performance enhancement and contributed to the reduction of waste heat exhausted to the atmosphere. Al-Azawie et al [22] considered different types of ground materials and presented the preliminary results of an experimental and numerical study on enhancing SCPP collector performance. They discussed and compared the results of the ground materials and concluded that the ceramic and the stone performed better than the other types of materials.…”
Section: Numerical Attemptsmentioning
confidence: 99%
“…The main input parameter in simulation was the solar irradiation, I which is assumed (100-1000 W/m 2 ) in steps 100 and the ambient temperature (30-34 o C). In the numerical model, the ground material was assumed painted black pebble with thickness of 0.1 m to increase the heat storage as recommended by [16] and underneath the pebble, the soil was considered 0.3 m thickness. As incompressible with constant viscosity, body force is acting in y-direction only.…”
Section: Description Of the Proposed Modelmentioning
confidence: 99%
“…In Malaysia, Al-Azawie et al [21] studied different materials as absorber under the collector by numerically and validated them with experiments. These materials were used to convert solar radiation to kinetic energy, which consisted of sawdust, blackstone, ceramic, pebble, sand, and dark green painted wood.…”
Section: Introductionmentioning
confidence: 99%